2013
DOI: 10.1159/000356903
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomy of the Human Hypothalamic Kisspeptin System

Abstract: Hypothalamic kisspeptin (KP) neurons are key players in the neuronal network that regulates the onset of puberty and the pulsatile secretion of gonadotropin-releasing hormone (GnRH). In various mammalian species, the majority of KP-synthesizing neurons are concentrated in two distinct cell populations in the preoptic region and the arcuate nucleus (ARC). While studies of female rodents have provided evidence that preoptic KP neurons play a critical sex-specific role in positive estrogen feedback, KP neurons of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 125 publications
(341 reference statements)
3
72
0
2
Order By: Relevance
“…1I-L). The ARC also contains tyrosine hydroxylase (TH)-positive neurons (Bluet-Pajot et al, 2001;Biebermann et al, 2012;Hrabovszky, 2014), and 15% of these cells are GHRH-neurons (Phelps et al, 2003). Interestingly, we also found that ∼76% of TH + neurons in the ARC express Isl1 at E16.5 and ∼23% of TH + neurons express Isl1 at P56 (Fig.…”
Section: Expression Of Isl1 In Developing Arcuate Nucleus Neuronsmentioning
confidence: 56%
See 2 more Smart Citations
“…1I-L). The ARC also contains tyrosine hydroxylase (TH)-positive neurons (Bluet-Pajot et al, 2001;Biebermann et al, 2012;Hrabovszky, 2014), and 15% of these cells are GHRH-neurons (Phelps et al, 2003). Interestingly, we also found that ∼76% of TH + neurons in the ARC express Isl1 at E16.5 and ∼23% of TH + neurons express Isl1 at P56 (Fig.…”
Section: Expression Of Isl1 In Developing Arcuate Nucleus Neuronsmentioning
confidence: 56%
“…Of note, most NPY + AgRP-neurons are known to be GABAergic, whereas most POMC neurons are non-GABAergic (Horvath et al, 1997;Ovesjo et al, 2001;Hentges et al, 2004). There are also other types of GABAergic neurons in the ARC, including a subset of kisspeptinneurons (Hrabovszky, 2014). Interestingly, more GABAergic neurons were observed in E14.5 Isl1 cko mice in comparison with control mice (Fig.…”
Section: Isl1mentioning
confidence: 87%
See 1 more Smart Citation
“…While homologous KP and NKB neurons are also present in the human infundibular nucleus [6,7], species differences are also likely to exist in the neurotransmitter complement that these neurons use for communication [8]. Notably, morphological studies have found only poor evidence for dynorphin expression in KP-immunoreactive (IR) neurons in the infundibular nucleus of young men [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings strongly suggest that ARC Kp neurons are critical for GnRH pulses [20][21][22][23][24] , whereas AVPV Kp neurons regulate preovulatory GnRH/LH surges [18,19,25] . Although anatomical differences have been observed across species (detailed discussion of the neuroanatomy of kisspeptin system in human is present in this special issue by Hrabovszky [26]), it is now widely accepted that Kp plays a pivotal role in regulating both GnRH pulses and surges in mammals [27] . Although Kp acts within the hypothalamus, several studies showed that peripheral Kp administration can stimulate GnRH neurons [7,[9][10][11][12] , presumably via circumventricular organs such as median eminence or the organum vasculosum of the lamina terminalis [28][29][30] , thus offering attractive therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%